Visual Analysis of Animal Experiments on Traditional Chinese Medicine (TCM) Nursing Technology Based on VOSviewer - MIAO Jinhuan; XU Xia; ZHOU Lu; CHENG Haiyan; HE Yan (Shiyan dongwu yu bijiao yixue, 2023)
Objective Through the visual analysis of animal experimental literature on Traditional Chinese Medicine (TCM) nursing technology, the relevant research hot spots were condensed and the research trends of relevant animal models were discussed, to provide reference for subsequent research.Methods The literature related to animal experiments on Chinese medicine nursing technology was retrieved from Wan Fang database, Chinese Science and Technology Journal Database (VIP), China National Knowledge Infrastructure Engineering Database (CNKI), China Biomedical Literature Database (CBM), PubMed and Web of Science until June 30, 2022. Visual analysis was performed using VOSviewer 1.6.17 software.Results A total of 1 864 articles in Chinese and 126 articles in English were included, with the number of annual publications increasing year by year. The relevant literature involved 18 TCM nursing techniques, with the largest number (426) involving massage having the highest number of articles. It involved 4 496 authors, out of whom 358 were core authors accounting for 7.9% of all authors, and had a total count of 3 706 keywords forming 7 clusters. The research hotspots mainly included massage treatment of inflammatory diseases and analgesic effect, acupoint injection treatment of allergic rhinitis and myocardial ischemia, acupoint application treatment of asthma-related respiratory diseases, and moxibustion treatment of inflammatory diseases. The study of the mechanism of abdominal massage on insulin resistance is the latest research topic among them.Conclusion In recent years, the animal model of abdominal massage has gained increasing popularity in animal experiments of TCM nursing techniques. However, the establishment and application of animal models related to Chinese medicine soaking and Chinese medicine hot ironing have not yet received attention. This area can be explored in the future to further improve the animal experimental research on Chinese medicine nursing technology.